Strategi Pendekatan Mahasiswa Terhadap Warga Desa Dilingkungan Sidap-Dap - Marpaung, Ernidawati; Hidayat, Muhammad (Journal of Community Sustainability, 2026)
Student engagement strategies with local residents in Sidap-Dap Village play a crucial role in fostering harmonious and productive relationships between academic communities and rural society. This study aims to identify and analyze effective approaches that enhance acceptance, participation, and collaboration of villagers in student-led activities such as community service programs, fieldwork (KKN), or other social initiatives. A qualitative method was employed, utilizing observation, interviews, and active participation techniques. The findings reveal that the most effective strategies include empathetic interpersonal communication, active involvement in local social and religious events, and adaptation to local cultural norms. A family-based and respectful approach toward local traditions proved to be the key to successful interaction between students and residents. This study contributes to the formulation of human-centered and sustainable engagement strategies that can also be applied in other rural contexts with similar characteristics.